Regional economic policy : proceedings of a conference - Minnesota Economics Association; Federal Reserve Bank of Minneapolis (Minneapolis : Federal Reserve Bank of Minneapolis, 1974)
This book is about a conference on Regional Economic Policy, it was one of several conferences sponsored by the bank to mark the year of their move to a new building. It also represented a significant cooperative effort, combining the annual meeting of the Minnesota Economic Association and the bank's biennial money and banking workshop.
Sponsored by the Minnesota Economics Association and the Federal Reserve Bank of Minneapolis on Nov. 2, 1973.
Includes bibliographical footnotes.
hza 27/06/2018
Loans
Keywords: Regional planning; Economic zoning; America